2023
DOI: 10.1093/stmcls/sxad013
|View full text |Cite
|
Sign up to set email alerts
|

How and Why the Circadian Clock Regulates Proliferation of Adult Epithelial Stem Cells

Abstract: First described in the early 20 th century, diurnal oscillations in stem cell proliferation exist in multiple internal epithelia, including in the gastrointestinal track, and in the epidermis. In the mouse epidermis, 3- to 4-fold more stem cells are in S-phase during the night than during the day. Work that is more recent showed that an intact circadian clock intrinsic to keratinocytes is required for these oscillations in epidermal stem cell proliferation. The circadian clock also regulates DNA excision repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…In these cells, G 2 /M cell cycle arrest was induced, and the apoptotic rate increased. At the same time, high-irradiance blue light decreased the expression levels of the BMAL1 and PER2 clock genes in the HaCaT cells, suggesting a circadian rhythm dysregulation [34][35][36]. High-irradiance red light did not induce cell death and did not alter the clock gene expression levels.…”
Section: Discussionmentioning
confidence: 77%
“…In these cells, G 2 /M cell cycle arrest was induced, and the apoptotic rate increased. At the same time, high-irradiance blue light decreased the expression levels of the BMAL1 and PER2 clock genes in the HaCaT cells, suggesting a circadian rhythm dysregulation [34][35][36]. High-irradiance red light did not induce cell death and did not alter the clock gene expression levels.…”
Section: Discussionmentioning
confidence: 77%
“…Studies in recent years have revealed the essential role for biological clocks in regulating stem cell circadian homeostasis [4][5][6][7][8][9]. Importantly, although a molecular circadian clock resides in almost all cells in in vivo and in vitro cultures, cells such as germline, zygote, and pluripotent stem cells (PSCs) show no discernible circadian rhythms of clock gene expression [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The skin can transmit light information to directly impact the circadian rhythm and proliferation of the epidermis. Light generally decreases proliferation: Light decreases epidermal stem cell numbers in S-phase of the cell cycle during the day compared to the night [10], reduces proliferation of cultured human melanocytes [11,12], and inhibits proliferation of pigmented cells in fish [13]. Opsins such as Opn3, Opn4 (Melanopsin), and Opn5 function as light sensors in mammalian pigment cells to regulate both pigment synthesis/intracellular movement [4,5,6] and melanocyte proliferation [14,15].…”
Section: Introductionmentioning
confidence: 99%